Multiple Splanchnic Venous Thromboses: A Fatal Complication of Recurrent Pancreatitis (Journal of Rangpur Medical College, 2023)
Splanchnic Venous Thrombosis (SVT) is a condition associated with high morbidity. The etiologies of SVT include intra-abdominal inflammation or infection, surgical intervention, abdominal malignancies such as hepatocellular carcinoma (HCC) and pancreatic carcinoma, or abnormality in coagulation caused by various reasons such as liver cirrhosis. Most cases of pancreatitis are mild and self-limited. On the other hand, approximately one-quarter of patients with pancreatitis may develop vascular complications such as venous thrombosis. Pancreatitis associated with vascular complications is dangerous and potentially fatal. The survival of patients with pancreatitis and vascular complications depends on the early detection of these complications. We report a case of a middle-aged male who had recurrent pancreatitis. On radiological imaging, the patient was found to have a portal vein, splenic vein, and superior mesenteric vein thrombosis. The etiology of thrombosis was considered to be inflammation around the main portal trunk caused by pancreatitis Patient recovered after emergent and timely management with initially low molecular weight heparin and bridged by oral apixaban therapy. The article focuses on the aspects of etiology, pathogenesis, diagnosis, and management of acute pancreatitis with venous thrombosis.J Rang Med Col. September 2023; Vol. 8, No. 2: 60-63